2009
DOI: 10.1523/jneurosci.4845-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Transporters Regulate Glutamate Clearance, NMDA Receptor Activation, and Synaptic Plasticity in the Hippocampus

Abstract: In the mammalian brain, the specificity of excitatory synaptic transmission depends on rapid diffusion of glutamate away from active synapses and the powerful uptake capacity of glutamate transporters in astrocytes. The extent to which neuronal glutamate transporters influence the lifetime of glutamate in the extracellular space remains unclear. Here we show that EAAC1, the predominant neuronal glutamate transporter at excitatory synapses in hippocampal area CA1, buffers glutamate released during synaptic even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
216
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(244 citation statements)
references
References 47 publications
13
216
1
1
Order By: Relevance
“…The kinetics of the fSTC are similar to the kinetics of the synaptically-activated transporter current (STCs) isolated pharmacologically with high concentrations of the glutamate transporter antagonist TBOA (100 μM) 13 . For this reason and for simplicity, in previous work, we referred to the fSTC as STC 13,14 . Despite being currents with similar properties, fSTCs and STCs are not the same current.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The kinetics of the fSTC are similar to the kinetics of the synaptically-activated transporter current (STCs) isolated pharmacologically with high concentrations of the glutamate transporter antagonist TBOA (100 μM) 13 . For this reason and for simplicity, in previous work, we referred to the fSTC as STC 13,14 . Despite being currents with similar properties, fSTCs and STCs are not the same current.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Because the clearance waveform rises from and decays back to zero, when the method was first established, there was no specification made on how to set the integration window, and in fact this was done rather loosely 13 . One way around this issue is to limit the integration window to the time it takes to reach an arbitrary proportion of the FTC/fSTC peak, for example 10% 14 . This simple criterion allows being consistent when performing this analysis in different cells, improves the accuracy in the estimates of <t> when the clearance waveform does not decay perfectly to zero, and improves the sensitivity of the analysis to small differences in clearance waveforms that might occur in different groups of cells.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the filtering of GLT currents by factors such as the electrotonic properties of astrocytes or the asynchronous transmitter release, which distort their kinetics 13 . Methods extracting the temporal features of the filtering mechanisms have been developed and can be used to derive the actual glutamate clearance time course in physiological or pathological situations, as recenly performed 6,13,14 . Additionally, the simultaneous recording of the astroglial membrane depolarization, in current clamp, can provide insights into possible alterations of extracellular potassium transients.…”
Section: +12mentioning
confidence: 99%
“…However, several studies have shown that EAAC1 has a negligible effect on glutamate clearance from brain extracellular space and that this function is performed primarily by the astrocyte glutamate transporters GLT1 and GLAST (glutamate-aspartate transporter) (Tanaka et al, 1997;Watase et al, 1998). Recent studies indicate a role for EAAC1 in regulating synaptic glutamate uptake (Scimemi et al, 2009); however, EAAC1 also functions as a highaffinity, concentrative cysteine transporter (Zerangue and Kavanaugh, 1996;Chen and Swanson, 2003;Himi et al, 2003;Watabe et al, 2008), and it is diffusely distributed over nonsynaptic neuronal membranes (Coco et al, 1997;Shashidharan et al, 1997). EAAC1 uptake of cysteine into neurons provides cysteine substrate for the synthesis of glutathione, the major thiol antioxidant Li and Maret, 2009).…”
Section: Introductionmentioning
confidence: 99%